The influence of audit fees and audit tenure on audit quality with financial distress as a moderating variable (A case study on Property and Real Estate Companies in 2018-2022) - Poluan, Lungchin; Sondakh, Jullie; Korompis, Claudia W. M. (The Contrarian : Finance, Accounting, and Business Research, 2025)
Audit quality is a crucial aspect that determines the reliability of financial statements and influences the economic decisions of stakeholders, where good audit practices can enhance transparency and trust in financial reports. In Indonesia's property and real estate sector, which involves complex transactions and high investment values, audit quality is essential to ensure the accuracy of financial statements and mitigate the risks of market fluctuations and regulatory changes that impact investment and funding decisions. The purpose of this study is to examine how audit fees and audit tenure affect audit quality and how financial distress moderates the relationship between independent and dependent variables. The population of this study consists of property and real estate companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling method used is simple random sampling, resulting in a sample of 50 companies. This study employs binary logistic regression analysis using SPSS version 29. The tests conducted include the overall model fit test, clarification matrix test, and hypothesis testing. The results show that audit fees do not significantly affect audit quality, audit tenure does not significantly affect audit quality, financial distress significantly moderates the relationship between audit fees and audit quality, and financial distress does not significantly moderate the relationship between audit tenure and audit quality.